Ontogeny and induction of adhesion molecule expression in human fetal intestine. - Doğan, A (1993)
In this study we examined the distribution of the adhesion molecules ICAM-1, VCAM-1 and E-selectin in human fetal intestine, to determine whether they may have a role in the development of gut-associated lymphoid tissue. Secondly, we studied the tempo of induction of these molecules after T cell activation in explants of human fetal intestine cultured in vitro. In the fetus from 11 to 20 weeks gestation, endothelial expression of ICAM-1 and diffuse staining of VCAM-1 was observed in the lamina propria. In contrast, there was intense expression of ICAM-1 and VCAM-1 in the developing Peyer's patches, suggesting that these molecules may be involved in the accumulation or organization of lymphoid tissue in the gut. After T cell activation in fetal intestinal explants, the expression of ICAM-1 and VCAM-1 was increased on most endothelial cells, leucocytes, and stromal cells in the lamina propria. Expression was maintained for at least 4 days. In contrast, the induction of E-selectin was rapid, and the expression was transient, despite the continuing presence of activated T cells and macrophages. This suggests that other factors are required to prevent the down-regulation of E-selectin to maintain the sustained expression sometimes observed in vivo.